Law and Happiness 2010
DOI: 10.7208/chicago/9780226676029.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Hive Psychology, Happiness, and Public Policy

Abstract: We consider three hypotheses about relatedness and well-being including the hive hypothesis, which says people need to lose themselves occasionally by becoming part of an emergent social organism in order to reach the highest levels of human flourishing. We discuss recent evolutionary thinking about multilevel selection, which offers a distal reason why the hive hypothesis might be true. We next consider psychological phenomena such as the joy of synchronized movement and the ecstatic joy of self-loss, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 19 publications
2
42
0
1
Order By: Relevance
“…All over the world and throughout history, people gather together to dance, sing, march, chant, and make music in time with one another. Such synchronization has often been hypothesized as a key mechanism in the purported solidarity‐enhancing effects of collective rituals (Durkheim, ; Ehrenreich, ; Fischer, Callander, Reddish, & Bulbulia, ; Haidt, Seder, & Kesebir, ; Wiltermuth & Heath, ). Recent laboratory studies have found converging evidence in support of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…All over the world and throughout history, people gather together to dance, sing, march, chant, and make music in time with one another. Such synchronization has often been hypothesized as a key mechanism in the purported solidarity‐enhancing effects of collective rituals (Durkheim, ; Ehrenreich, ; Fischer, Callander, Reddish, & Bulbulia, ; Haidt, Seder, & Kesebir, ; Wiltermuth & Heath, ). Recent laboratory studies have found converging evidence in support of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Large–scale synchronous behavior—marching, dancing, or singing—can enthuse, inspire, mesmerize, or frighten, and has been part of rituals and traditions across the world over centuries (Haidt, Seder, & Kesebir, ; Vicary et al., ). Rituals bind people together (Whitehouse & Lanman, ), emphasizing group membership and commitment to the group (McNeill, ), as well as facilitating cooperation (Watson‐Jones & Legare, ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of individuals in fact does not behave as "economic man", but have strong moral and social preferences, as revealed by a host of studies involving the Prisoners' Dilemma and other types of experimental scenarios (see, e.g., Hibbing and Alford 2004;Bowles 2016). Indeed, people have both the ability and the inclination to suppress selfish behavior in order to form complex societies that presuppose human cooperation (Haidt, Seder, and Kesebir 2008). They also strive for meaning and satisfaction in their work and their endeavors, that have little to do with shortsighted material gain (Csíkszentmihályi 1992).…”
Section: Markets and Moralitymentioning
confidence: 99%